2018
DOI: 10.3892/mco.2018.1668
|View full text |Cite
|
Sign up to set email alerts
|

Age‑related differences in prognosis and prognostic factors among patients with epithelial ovarian cancer

Abstract: Approximately 40% of all patients with ovarian cancer in Japan are aged ≥65 years. The aim of the present study was to evaluate the differences in prognosis and prognostic factors between elderly and younger patients with epithelial ovarian cancer. A total of 114 patients with International Federation of Gynecology and Obstetrics (FIGO) stage I-IV ovarian cancer who were initiated on primary treatment at the Osaka City University Hospital (Osaka, Japan) were included in this study. Patient characteristics, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Different prognostic factors have been mentioned in younger and elderly patients in a previous study. The FIGO stage and standard primary treatment were independent determinants in younger women, whereas performance status was identified as the independent determinant in elderly women 22 . On the other hand, another study showed higher survival rates for very young EOC patients compared to young or older groups 23 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Different prognostic factors have been mentioned in younger and elderly patients in a previous study. The FIGO stage and standard primary treatment were independent determinants in younger women, whereas performance status was identified as the independent determinant in elderly women 22 . On the other hand, another study showed higher survival rates for very young EOC patients compared to young or older groups 23 .…”
Section: Discussionmentioning
confidence: 93%
“…The FIGO stage and standard primary treatment were independent determinants in younger women, whereas performance status was identified as the independent determinant in elderly women. 22 On the other hand, another study showed higher survival rates for very young EOC patients compared to young or older groups. 23 This result might be related to the medical and physiological conditions which might be present in older EOC patients and require special attention in planning treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…18 However, the high heterogeneity of elderly patients means that it is not feasible to make treatment decisions based on age alone, and a more objective assessment is required. 19 Weaknesses in this study are that researchers cannot control the state and quality of data that have been done by others in the past and the research can only rely on secondary data that is already in incomplete medical record records where the possibility of errors in recording or available data is not appropriate with what is needed in research. For this reason, better records are needed for ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%